Philosophical basis of ecological education (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the philosophical foundations of environmental education. Appeal to the philosophical foundations of environmental education in the relationship of the system “human-society-nature” leads to the development of a certain methodology, value orientations, conceptual paradigms of worldview and knowledge that determine socio-cultural, environmental and other processes. The ultimate goal of environmental education is the creation of optimal environmental conditions for the life of humanity by forming an environmental culture and preserving natural values.
Keywords: nature, environmental problems, environmental education, philosophy